Acute and long-term effects of stroboscopic training on sport performance: A systematic review and meta-analysis - Vera, J.; Cantó-Cerdán, M.; García-Ramos, A.; Redondo, B. (Journal of Sports Sciences, 2026)
Stroboscopic training is increasingly used to enhance athletes` perceptual and motor skills, but its impact on sport-specific performance remains unclear. This systematic review and meta-analysis assessed short- and long-term effects of stroboscopic training on performance metrics, focusing on response accuracy and time. Following PRISMA guidelines (PROSPERO code: CRD420251027637), four databases were searched through April 2025. Studies were eligible if peer-reviewed, in English, and evaluated sport performance during or after stroboscopic training. Risk of bias was assessed with a modified Downs and Black tool. Standardized mean differences (SMDs) were computed using fixed- or random-effects models, depending on heterogeneity. Seventeen studies met inclusion criteria. Acute stroboscopic exposure led to moderate performance decrements in response accuracy (SMD = 0.50; 95% CI: 0.19-0.81) and response time (SMD = 0.51; 95% CI: 0.17 to 0.86). In contrast, long-term training produced significant improvements in response accuracy (SMD = -0.71; 95% CI: -1.41 to -0.02) and response time (SMD = -1.10; 95% CI: -2.11 to -0.08), equating to gains of 5.7% and 5.3%, respectively. Stroboscopic training enhances long-term sport-specific performance, whereas despite initial performance decrements during training. These findings highlight its value as a perceptual training strategy in fast-paced sports. Future research should standardise protocols and investigate the underlying neurophysiological mechanisms.